Pulse volume recordings to identify falsely elevated ankle brachial index. (July 2016) - Shirasu, Takuro; Hoshina, Katsuyuki; Akagi, Daisuke; Miyahara, Takuya; Yamamoto, Kota; Watanabe, Toshiaki
Background: Ankle brachial index can be falsely elevated in cases of medial arterial calcification, and its clinical use should be limited, especially in patients with diabetes. The aim of this study was to evaluate the potential role of pulse volume recording in detecting falsely elevated ankle brachial index. Methods: Two parameters of the pulse waveform were automatically calculated: upstroke time and percentage mean artery pressure. Pulse volume recordings were retrospectively evaluated in 171 consecutive patients (342 limbs); 73 (43%) had a diagnosis of diabetes. Results: On multivariate analysis, diabetes (hazard ratio = 1.7), ankle brachial index ≤ 0.90 (hazard ratio = 4.4), upstroke time ≥ 180 ms (hazard ratio = 2.1), and percentage mean artery pressure ≥ 45% (hazard ratio = 2.8) were significantly related to toe brachial index < 0.60. Further analysis for falsely elevated ankle brachial index was performed in 196 limbs (146 patients) with ankle brachial index > 0.90. The difference between ankle brachial index and toe brachial index differentiated the limbs of diabetic patients, with percentage mean artery pressure ≥ 45%, from controls (0.45 ± 0.17 vs. 0.35 ± 0.16, p  = 0.03); upstroke time was not found to be a discriminating factor. Conclusions: Although measurement of ankle brachial index remains the gold standard for diagnosing peripheral arterial disease, percentage mean artery pressure, automatically obtained in ankle brachial index measurement, may be useful to detect falsely elevated ankle brachial index, especially in patients with diabetes.